2016
DOI: 10.1007/s12205-016-0637-8
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on load transfer effect of Stiffened Deep Mixed column-supported embankment over soft soil

Abstract: A new composite column technique referred to as Stiffened Deep Mixed (SDM) column has been adopted to support embankment over soft soil to mitigate the post-construction settlement, increase bearing capacity and enhance stability. The SDM column was formed by inserting a precast concrete core pile into the center of a Deep Mixed (DM) column immediately after the construction of DM column. Due to the complicate interaction between concrete core pile, DM column and surrounding soil, the load transfer mechanism b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…They found the tension to be highest at the centerline and near zero at the shoulder and concluded that the results were affected by inadequate development length in the reinforcement. Research using numerical techniques has focused on the CSE vertical load distribution between columns and subsoil, but not on the lateral thrust distribution in the embankment, foundation, and geosynthetic reinforcement (Ariyarathne et al 2013a, b;Bhasi and Rajagopal 2013Borges and Marques 2011;Han and Gabr 2002;Huang andHan 2009, 2010;Jamsawang et al 2016;Jenck et al 2009;Liu et al 2007;Liu and Rowe 2016;Mahdavi et al 2016;Nunez et al 2013;Rowe and Liu 2015;Stewart et al 2004;Ye et al 2016;Yu et al 2016;Zheng et al 2009;Zhuang and Wang 2016). In this study, a numerical parametric study was used to analyze the lateral thrust distribution of CSEs for a wide range of conditions.…”
Section: Study Motivationsmentioning
confidence: 99%
“…They found the tension to be highest at the centerline and near zero at the shoulder and concluded that the results were affected by inadequate development length in the reinforcement. Research using numerical techniques has focused on the CSE vertical load distribution between columns and subsoil, but not on the lateral thrust distribution in the embankment, foundation, and geosynthetic reinforcement (Ariyarathne et al 2013a, b;Bhasi and Rajagopal 2013Borges and Marques 2011;Han and Gabr 2002;Huang andHan 2009, 2010;Jamsawang et al 2016;Jenck et al 2009;Liu et al 2007;Liu and Rowe 2016;Mahdavi et al 2016;Nunez et al 2013;Rowe and Liu 2015;Stewart et al 2004;Ye et al 2016;Yu et al 2016;Zheng et al 2009;Zhuang and Wang 2016). In this study, a numerical parametric study was used to analyze the lateral thrust distribution of CSEs for a wide range of conditions.…”
Section: Study Motivationsmentioning
confidence: 99%
“…The bearing performances of the PCCS were investigated by means of experimental, theoretical, and numerical analysis under vertical and lateral loads [26][27][28][29][30][31]. The inner core is installed to bear external loads, while the outer core can increase the shaft friction of the inner core and effectively transfer the inner core's axial force to the surrounding soil [18].…”
Section: Introductionmentioning
confidence: 99%
“…Based on tested results, Wang et al [33] found that the stiffened deep mixing (SDM) column-supported embankment could significantly reduce the postconstruction settlement by 27.3%-68.3 compared to the conventional DM column-reinforced composite foundation. Ye et al [26] established a series of finite element (FE) models to analyze the bearing mechanism of the SDM column-supported embankment.…”
Section: Introductionmentioning
confidence: 99%
“…Numerical simulation is an effective tool for analyzing complex engineering problems, especially the pile-soil interaction. rough numerical analysis, Ye et al [7][8][9] discussed load transfer law and the effect of reinforced core on the performance and failure behavior of stiffened deep cement mixing piles. Based on the engineering application of PPEB pile technology in Zhejiang Province, China, Yang et al [10], Zhou et al [11], and Xie et al [12] used the numerical simulation method to analyze the influence of structure size of precast pile, soil properties, cement soil characteristics, and other factors on bearing capacity, which enriched the understanding of the characteristics of PPEB piles.…”
Section: Introductionmentioning
confidence: 99%